Structural Analysis of Brake Shoe under Static Load Using Al Alloy, Cast Iron, Mg Alloy for Main Components, and Carbon Variants for Brake Linings - Dony Eko Prasetyo; Hadi Sutanto; Arka Dwinanda Soewono (Automotive Experiences, 2024)
The research is motivated by the issue faced by motorcycle users, namely the wear and tear of brake shoes, which can reduce braking effectiveness and increase the risk of accidents. The main objective of this study is to analyze the structural properties of motorcycle brake shoes with three different materials (aluminum alloy, cast iron, and magnesium alloy) and brake linings made of different carbon variants (alumina-carbon composite, carbon ceramics, and carbon fiber) under static pressures. Additional design aspects including weight and production cost are also evaluated during the material selection process for the motorcycle’s brake shoe and brake lining. The 3D modeling of the brake shoe and lining was done in Solidworks using measurement data from a Coordinate Measuring Machine (CMM). The finite element analysis was performed using ABAQUS software. Considering the results from the finite element analysis, weight, and economic aspects, the study found that aluminum alloy (Al alloy) and carbon composite can be suitable materials for brake shoes and brake lining. The Al alloy brake shoe provides 62.7% weight saving while exhibiting good structural properties under static load and a moderate increase in production cost compared to cast iron. Similarly, brake lining with alumina-carbon composite showed the least deformation under static load while maintaining modest production costs compared to the other carbon variants.